2015
DOI: 10.1111/jce.12741
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐Based Electromagnetic Navigation (Mediguide®): How Accurate Is It? A Phantom Model Study

Abstract: The MediGuide® system shows a very high level of accuracy regarding localization reproducibility as well as spatial and visual accuracy, which can be ascribed to the magnetic field localization technology. The observed offsets between the geometry visualization and the real phantom are below a clinically relevant threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…As of January 2015, software updates rendered it possible to adopt lower‐dose fluoroscopy settings (i.e., 3 instead of 6 fps and 23 instead of 40 nGy/pulse, both with an 8.0‐millisecond pulse duration), which were systematically adopted in all 3 EP labs and applied to all patients. Details about the MDG technology, its interface, potential applications, and the technique for CRT implantation have been previously described . In brief, the system consists of 3 components: a transmitter that generates a 3D electromagnetic field, an electromagnetic reference patch positioned on the patient's chest, and a miniaturized sensor incorporated within the LV‐related implant tool (e.g., guiding sheath, sub‐selection catheter, decapolar CS catheter, and 0.014" guide‐wire).…”
Section: Methodsmentioning
confidence: 99%
“…As of January 2015, software updates rendered it possible to adopt lower‐dose fluoroscopy settings (i.e., 3 instead of 6 fps and 23 instead of 40 nGy/pulse, both with an 8.0‐millisecond pulse duration), which were systematically adopted in all 3 EP labs and applied to all patients. Details about the MDG technology, its interface, potential applications, and the technique for CRT implantation have been previously described . In brief, the system consists of 3 components: a transmitter that generates a 3D electromagnetic field, an electromagnetic reference patch positioned on the patient's chest, and a miniaturized sensor incorporated within the LV‐related implant tool (e.g., guiding sheath, sub‐selection catheter, decapolar CS catheter, and 0.014" guide‐wire).…”
Section: Methodsmentioning
confidence: 99%
“…The heartbeat is simulated through water or air pumps, with functional parameters similar to the physiological ones. Recently, some authors focused on atrial phantom models . These models were mainly used for training/planning of cardiac ablations, presenting the atrial body and the proximal part of the pulmonary veins.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors focused on atrial phantom models. 11,18,19 These models were mainly used for training/planning of cardiac ablations, 19,20 presenting the atrial body and the proximal part of the pulmonary veins. Nevertheless, these solutions were either rigid 19 or not appropriate for ultrasound (US) acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…It is influenced by impedance changes and differences in tissue types. Studies demonstrated that electromagnetic catheter localization offers a higher level of accuracy as it operates independently from tissue properties compared to impedance measurement‐based electric catheter localization . Recently, the next‐generation novel mapping system, EnSite Precision mapping system (St. Jude Medical, Inc.) was introduced, which combines both impedance and magnetic technologies.…”
Section: Introductionmentioning
confidence: 99%